Congenital Duodenal Obstruction, Situs Inversus Totalis, and Gastric Perforation in a Neonate - Piplani, Rajat (J Neonatal Surg, 2017)
We report a rare case of incomplete congenital duodenal obstruction (Type 1 duodenal atresia) in association with situs inversus totalis presenting with gastric perforation in a neonate. The infantogram was suggestive of perforation with air under diaphragm along with dextrocardia. On exploration, a pin point perforation at fundus near lesser curvature along with situs inversus was noted. Primary closure of gastric perforation was done. Patient was then discharged on full breast feeds but was readmitted with intolerance to feeds and recurrent bilious vomiting. Further, upper GI contrast study revealed partial duodenal obstruction. On re-exploration, duodenal web with central aperture was seen and duodeno-duodenostomy was done.